Why is the accumulation of knowledge so hard? Exploring econometric research on the determinants of public social spending in Latin America - Flechtner, S; Sanchez-Ancochea, D (Cambridge University Press, 2022)
Many areas in applied econometric research within political economy fail to come up with conclusive findings. This is the case, for example, with studies on the determinants of public social spending in Latin America, a key area of research given the impact of social programs on poverty, inequality, and welfare more generally. In this area, as in others, it is hard to identify clear answers regarding the impact of economic processes and political institutions. Two reasons explain this lack of knowledge accumulation. First, each study uses different data sources and analytical models. Second, some of the empirical strategies required to solve various econometric problems may affect the results. This article questions the role of econometric research as the only method to explore political economy questions and highlights the importance of promoting conversations between complementary methods of both quantitative and qualitative traditions. Buena parte de la investigación econométrica dentro de la economía política no obtiene resultados conclusivos. Este es, por ejemplo, el caso de los estudios sobre los determinantes del gasto social en América Latina, un área importante de investigación dado el impacto de los programas sociales en la pobreza, la desigualdad y, más en general, el bienestar. En este campo, como en otros, es difícil identificar respuestas definitivas sobre al impacto de los procesos económicos y las instituciones políticas. Hay dos razones principales que explican esta falta de acumulación de conocimiento en este caso. Primero, cada estudio utilizada fuentes estadísticas y modelos analíticos distintos. Segundo, algunas de las estrategias empíricas adoptadas para resolver distintos problemas econométricos pueden afectar a los resultados. Así, nuestro análisis cuestiona el papel de la econometría como el método único para explorar preguntas de economía política y muestra la importancia de promover conversaciones entre métodos cualitativos y cuantitativos complementarios.